Selective Treatment of PDA in High-Risk VLBW Infants With Birth Weight ≤800 g or <27 Weeks and Short-Term Outcome: A Cohort Study - Ibrahim, Thowfique; Abdul Haium, Abdul Alim; Tapawan, Sarah Jane; Dela Puerta, Rowena; Allen, John C.; Chandran, Suresh; Chua, Mei Chien; Rajadurai, Victor Samuel (Frontiers in Pediatrics, 2021)
Background: Patent ductus arteriosus (PDA) causing significant left to right shunt can increase key morbidities in preterm infants. Yet, treatment does not improve outcomes and spontaneous closure is the natural course of PDA. Impact of PDA on 23-26-week gestation infants is uncertain. Selective treatment of such infants would likely balance outcomes. Hypothesis: Treatment of PDA in high- risk VLBW infants [birth weight ≤ 800g or gestation <27 weeks, hemodynamically significant, ductal diameter (DD, ≥1.6mm) and mechanical ventilation] and expectant management in low-risk infants will reduce the need for treatment and surgical ligation, without altering short term morbidities. Methods: This prospective observational study was initiated subsequent to the introduction of a new treatment protocol in 2016. The 12-months before and after protocol introduction were respectively defined as control and treatment periods. In the treatment cohort, PDA was treated with indomethacin, maximum of 2 courses, one week apart. Surgical ligation was considered after 30 days of age if indicated (DD ≥2mm, mechanical ventilation). Primary outcomes were need for treatment and rate of ligation. Protocol compliance and secondary outcomes were documented. Results: 415 infants were studied, 202 and 213 in the control and treatment cohorts, respectively. Numbers treated (per protocol) in the control and treatment cohorts were 27.7% and 19.3% (56/202 and 41/213) (p=0.049), and the respective ligation rates were 7.54% and 2.96% (P=0.045). Secondary outcomes were comparable. Conclusion: The selective treatment protocol reduced the rates of treatment and surgical ligation of PDA, without altering key morbidities. Further studies under a randomized control trial setting is warranted